Being a man: some reflections from masculinities - Vasquez del Aguila, Ernesto (Política y Sociedad, 2013)
This paper highlights some reflections based on empirical research conducted by the author over more than fifteen years with Latin American men, across a range of locations, including Lima, Peru; Buenos Aires, Argentina; New York, USA; and Dublin, Ireland. These reflections show the complexities of becoming men for boys and adolescents in different cultural contexts. The paper integrates classic and contemporary articles about masculinities produced by Latin American researchers and articles from the so-called Global North.